Implementasi Model Pembelajaran Kooperatif Tipe Numbered Head Together (NHT) yang Mengintegrasikan Peer - Assessment untuk Meningkatkan Keterampilan Sosial Peserta Didik - Adawiyah, Siti Rabiatul (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
This study aims to determine the role of the application of the Numbered Head Together (NHT) cooperative learning model that integrates peer-assessment to improve students' social skills. The peer-assessment instrument was developed using the Dick and Carey model. The trial of the peer-assessment instrument that has been developed was carried out at the MA Annajah Al-Halimy Education Foundation, West Lombok Regency. The peer-assessment instrument that has been developed is focused on assessing the social skills of students. The research data were analyzed descriptively. Assessment of students' social skills using peer-assessment is carried out at each meeting, namely for 4 meetings. The results showed that the social skills of students tended to increase at each meeting, namely: 4; 4.2; 4.3; and 4.4.